Pengaruh Label Halal Pada Kemasan Obat Herbal Terhadap Keputusan Pembelian Di Apotek Cangkiran - Arfianto, Erki; Marceilha, Nadya; Ningtyas, Ery Ardiyanti (Jurnal Farmasi & Sains Indonesia, 2025)
Considering that the majority of Indonesia's population is Muslim, pharmaceutical products must have halal certification and labeling. Consuming something halal is a mandatory thing for Muslims. Use of herbal medicine When consuming a herbal medicine product, one must pay attention to the halal status of the medicine by seeing whether there is a halal logo on the herbal medicine. The purpose of this study was to determine whether the halal label of herbal medicine influences consumer purchasing decisions at the Cangkiran Pharmacy and to determine the level of public knowledge of the halal label. This type of research uses a quantitative descriptive approach with a sampling technique method using purposive sampling. The instrument used is a questionnaire with validation and reliability tests. The results of the study showed that the results of the validation test were declared valid and the reliability test was declared reliable or trustworthy. for questionnaire questions showed the highest average percentage, namely agree (ST). This can indicate that the decision to buy halal-labeled herbal medicine is largely influenced by the halal label.